Marketing estratégico para el incremento de ventas en el Concesionario Vallejo Araujo, ciudad de Guayaquil - Diez Zambrano, Bárbara del Roció (2023)
The Vallejo Araujo dealership faces a low number of sales despite the various strategies carried out within the automobile market in the city of Guayaquil. The scant interaction between the dealer and its target audience influences the purchase decision and the positioning of the commercial house in the mind of the consumer as the first purchase option. For this reason, the objective was: to establish strategic marketing to increase sales in the Vallejo Araujo dealership, Guayaquil city. Within the applied methodology, this was based on the quantitative and qualitative aspects, this being a mixed approach for the collection and analysis of much more information, linking both data in the same study, aimed at professionals trained in the strategic environment such as managers, bosses, and professionals in the area allowing us an interview with a questionnaire previously carried out and carefully analyzed that allows obtaining the most professional information in the best way, it should be noted that the survey was also used with another questionnaire for the consumer, in order to understand their behaviors and thus improve the strategies to be implemented in the form of proposals. Finally, it was concluded that through the readjustment of certain internal and external activities of the Vallejo Araujo concessionaire in the city of Guayaquil, it was possible to show a growth of 20% in each of the periods projected by the implementation of marketing activities.